2016
DOI: 10.1016/j.jshs.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between intermittent limit cycles and postural instability associated with Parkinson's disease

Abstract: BackgroundMany disease-specific factors such as muscular weakness, increased muscle stiffness, varying postural strategies, and changes in postural reflexes have been shown to lead to postural instability and fall risk in people with Parkinson's disease (PD). Recently, analytical techniques, inspired by the dynamical systems perspective on movement control and coordination, have been used to examine the mechanisms underlying the dynamics of postural declines and the emergence of postural instabilities in peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…This study suggests that dysfunction in sway control systems contributes to the pathophysiology of balance impairment in Parkinson’s disease and is potentially reversible with therapy, at least in patients similar to those studied here. It has been relatively unexplored whether such control systems are dysfunctional in Parkinson’s disease and contribute to the pathophysiology of balance impairment (Maurer et al , 2004; Yamamoto et al , 2011; Chagdes et al , 2016). Here, we explicitly measured feedback gains according to the PID model of continuous control and calculated the frequency of intermittent switching behaviour in the sway dataset (Hidenori and Jiang, 2006; Nema et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggests that dysfunction in sway control systems contributes to the pathophysiology of balance impairment in Parkinson’s disease and is potentially reversible with therapy, at least in patients similar to those studied here. It has been relatively unexplored whether such control systems are dysfunctional in Parkinson’s disease and contribute to the pathophysiology of balance impairment (Maurer et al , 2004; Yamamoto et al , 2011; Chagdes et al , 2016). Here, we explicitly measured feedback gains according to the PID model of continuous control and calculated the frequency of intermittent switching behaviour in the sway dataset (Hidenori and Jiang, 2006; Nema et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…how quickly deficits are made up and how much oscillation occurs). A range of indirect phenomena have suggested that continuous sway control systems may be affected in Parkinson’s disease, for example the detection of abnormal resonance in sway including limit cycle oscillations (Maurer et al , 2004; Chagdes et al , 2016). However, there is a lack of research directly addressing whether PID error signal processing in the control of sway is affected by Parkinson’s disease and its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, arguments based on a control-system analogy were used to support the hypothesis that Parkinsonian tremor may indeed be a limit cycle oscillation [1], and established a direct logical connection between increased response time and limit-cycle behaviour of Parkinsonian tremor. Since then, similar connections between increased time delays and limit cycle oscillations in human biomechanics (although not necessarily in the context of Parkinson's disease) have also been drawn [17,18,19]. In this paper, we exploit this link between increased time delays (observed as an increase in response times) and Parkinsonian tremors to address two specific objectives (see Fig.…”
Section: Introductionmentioning
confidence: 86%
“…The non-linear coupling between components generates behaviors that cannot be explained using traditional models. Therefore, the term “emergence” is often used when studying non-linear dynamic systems for the apparent pattern change due to the interactions of the system's components 7 . Bifurcation is one of the examples that sudden abrupt changes could happen within the non-linear system 4 .…”
mentioning
confidence: 99%
“…The authors demonstrated that MSE can be used to identify functional changes in posture fluctuations between clinically different subgroups of children with adolescent idiopathic scoliosis, and “loss of complexity hypothesis ” in cases of aging and disease related declines in physiological functions. Further, Chagdes and co-workers 7 demonstrated the emergence of limited cycle oscillators among people with mild Parkinson's disease using non-linear parameters generated from anterior–posterior postural sway.…”
mentioning
confidence: 99%